Breaching Biological Barriers: Protein Translocation Domains as Tools for Molecular Imaging and Therapy - Benjamin L. Franc; Stefanie J. Mandl; Zurab Siprashvili; Paul Wender; Christopher H. Contag (Molecular Imaging)
The lipid bilayer of a cell presents a significant barrier for the delivery of many molecular imaging reagents into cells at target sites in the body. Protein translocation domains (PTDs) are peptides that breach this barrier. Conjugation of PTDs to imaging agents can be utilized to facilitate the delivery of these agents through the cell wall, and in some cases, into the cell nucleus, and have potential for in vitro and in vivo applications. PTD imaging conjugates have included small molecules, peptides, proteins, DNA, metal chelates, and magnetic nanoparticles. The full potential of the use of PTDs in novel in vivo molecular probes is currently under investigation. Cells have been labeled in culture using magnetic nanoparticles derivatized with a PTD and monitored in vivo to assess trafficking patterns relative to cells expressing a target antigen. In vivo imaging of PTD-mediated gene transfer to cells of the skin has been demonstrated in living animals. Here we review several natural and synthetic PTDs that have evolved in the quest for easier translocation across biological barriers and the application of these peptide domains to in vivo delivery of imaging agents.